Vulnerability of Special Agreements Signed by NonState Armed Groups in Non-International Conflicts* (2019)
International law has recognized the existence and legal force of special agreements signed by non-state armed groups —NSAG — in the context of non-international armed conflicts -NIAC-. Nevertheless, considering the poor development of this area in International Law, praxis evidences that national governments bring a different legal treatment to those instruments. In consequence, there is not a clear path to oblige the parties to fulfill what they internationally have agreed to. This paper aims to establish the vulnerability of special agreements as result of the lack of protection from international law. As main discussion points, it is approached: a) the legal capacity of non-state actors, b) the legal treatment that international law confers to these legal instruments and c) review of some cases.